Engineering the Growth of MoS2 via Atomic Layer Deposition of Molybdenum Oxide Film Precursor. (19th September 2016) - Martella, Christian; Melloni, Pierpaolo; Cinquanta, Eugenio; Cianci, Elena; Alia, Mario; Longo, Massimo; Lamperti, Alessio; Vangelista, Silvia; Fanciulli, Marco; Molle, Alessandro
Abstract : The growth of atomically thin MoS2 films is achieved by sulfurization of molybdenum oxide precursor films grown by atomic layer deposition. The quality features of the MoS2 films are engineered controlling the stoichiometry, morphology, and thickness of the precursors. The interface interaction between the precursor films and the substrates (SiO2 or sapphire) plays a key role in the MoS2 formation.